Improved stomatal opening enhances photosynthetic rate and biomass production in fluctuating light. (25th February 2020) - Kimura, Haruki; Hashimoto-Sugimoto, Mimi; Iba, Koh; Terashima, Ichiro; Yamori, Wataru
Abstract: It has been reported that stomatal conductance often limits the steady-state photosynthetic rate. On the other hand, the stomatal limitation of photosynthesis in fluctuating light remains largely unknown, although in nature light fluctuates due to changes in sun position, cloud cover, and the overshadowing canopy. In this study, we analysed three mutant lines of Arabidopsis with increased stomatal conductance to examine to what extent stomatal opening limits photosynthesis in fluctuating light. The slac1 ( slow anion channel-associated 1 ) and ost1 ( open stomata 1 ) mutants with stay-open stomata, and the PATROL1 ( proton ATPase translocation control 1 ) overexpression line with faster stomatal opening responses exhibited higher photosynthetic rates and plant growth in fluctuating light than the wild-type, whereas these four lines showed similar photosynthetic rates and plant growth in constant light. The slac1 and ost1 mutants tended to keep their stomata open in fluctuating light, resulting in lower water-use efficiency (WUE) than the wild-type. However, the PATROL1 overexpression line closed stomata when needed and opened stomata immediately upon irradiation, resulting in similar WUE to the wild-type. The present study clearly shows that there is room to optimize stomatal responses, leading to greater photosynthesis and biomass accumulation in fluctuating light in nature. Abstract : Plants with greater stomatal opening or with stomata with faster light-dependent opening exhibited higher photosynthetic rates and growth under fluctuating light conditions.